Az orosz tőkeexport és az eklektikus paradigma jövője: Mi változik a 2008–2009. évi válság után? - Kalotay, Kálmán (Competitio, 2010)
This article explores the future of Russian outward foreign direct investment in the aftermath of the crisis of 2008–2009. As it is too early to analyse the full impact of the crisis, it develops hypotheses about the degree of slowdown in the foreign expansion of Russian transnational corporations. It uses an extension of the eclectic paradigm to home country advantages (competitive environment, business environment, development strategy, State involvement) applied to a comparison of the Russian Federation with other economies in transition as an analytical tool. Systematic differences between transnationals from the Russian Federation (global firms, based on natural resources, aiming for vertical integration of assets) and from new European Union member countries (regional firms, based on downstream activities or services, aiming for horizontal integration) allow us to formulate more solid conclusions about the future of the Russian firms facing lower export prices, lower market capitalizations and higher debts. In turn, this article argue that a comparison with the large emerging economies of Brazil, China and India, under the acronym of BRIC can be less useful in the current context, as these economies are significantly less affected by the crisis of 2008–2009 than the Russian Federation; hence they can not expect a slowdown in their outward foreign direct investment similar to that of Russian transnationals.JEL: F23; F21; O52; P29